Research on Power Grid Investment Risk of Set-Analysis Method in New Electricity Reform - Lu Jianchang; Xing Dandan (MATEC Web of Conferences, 2018)
In view of the change in the profit model of the power grid under the new power reform, If grid companies want to improve their economic efficiency, they must expand the scale of effective assets of fixed assets and increase the number of effective assets within the understanding of the demand for electricity.By determining the factors affecting the power grid investment in the new environment,a risk model for the power grid investment under the new power reform is constructed.First,this paper uses the set pair analysis method algorithm and derives the relevant formula to quantify uncertainties in grid investment risk.Then,it gets the results of the calculation of the degree of connection of each scheme and combine set pair events with a net present value less than 0 for each set evens.At last,based on the above results,we get the best investment plan.Verified by the case of the HBN grid company,it shows that the investment risk model established is feasible and can provide an appropriate reference for the new power companies to change their investment decisions.